Employee Commitment to Organizational Change with the Role of Job Satisfaction and Transformational Leadership - Nguyen Thi Bich Thuy; Phan Dang Ngoc Yen Van (Technium Social Sciences Journal, 2021)
This study aimed to analyze the role of job satisfaction and transformation leadership for employees’ commitment to organizational change. Based on a survey sample of 381 employees in post-merger enterprises in retail and pharmaceutical sector and a linear regression model. The results revealed that Transformational leadership was associated positively and significantly with Affective Commitment (? = .42, p < .000), Normative Commitment (? = .32, p < .000), and Continuance Commitment (? = .27, p < .000); Job satisfaction was associated positively and significantly with Affective Commitment (? = .24, p < .000) and Normative Commitment (? = .30, p < .000) among employees’ to organizational change. The results of this study provide a foundation of theory and practice for organizational changes that can efficiently exploit the human resource for the development in the next period.